2017
DOI: 10.5812/ijpbs.7700
|View full text |Cite
|
Sign up to set email alerts
|

How Gender, Majors, Religion and Mental Health Affect the Justified Death Attitude?

Abstract: Background: Death penalty and euthanasia are disputed practices in the world. However, they are considered "justified" by their proponents. We newly developed a scale for assessment of the attitude toward justified death, which determines "hot cognition" using a number of scenarios. Objectives: This study aimed at assessing the effects of the major demographic items including gender, major, religion, and mental health on the justified death attitude. Methods: A total of 481 participants including 419 universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(36 reference statements)
0
1
1
Order By: Relevance
“…Although, most studies suggested that gender is an effective factor in the attitude toward euthanasia 12,13,17 and male participants had a more positive attitude toward euthanasia. 12,13,32 In the present study, there was no statistically significant relationship between work experience of nurses and their attitude toward euthanasia. Naseh et al 3 reported no significant relationship between attitude toward euthanasia and nurses' work experience.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although, most studies suggested that gender is an effective factor in the attitude toward euthanasia 12,13,17 and male participants had a more positive attitude toward euthanasia. 12,13,32 In the present study, there was no statistically significant relationship between work experience of nurses and their attitude toward euthanasia. Naseh et al 3 reported no significant relationship between attitude toward euthanasia and nurses' work experience.…”
Section: Discussioncontrasting
confidence: 73%
“…14 Religious beliefs are the most important predictor of attitude toward euthanasia, and religious people have a more negative attitude toward euthanasia. [2][3][4]17,32 In the present study, in order to study the role of religion more accurately, it could be helpful to measure the level of religiosity of nurses.…”
Section: Discussionmentioning
confidence: 99%